On Leibniz - Rescher, Nicholas (University of Pittsburgh Press, 2013)
Contemporary philosopher John Searle has characterized Gottfried Wilhelm Leibniz (1646-1716) as "the most intelligent human being who has ever lived." The German philosopher, mathematician, and logician invented calculus (independently of Sir Isaac Newton), topology, determinants, binary arithmetic, symbolic logic, rational mechanics, and much more. His metaphysics bequeathed a set of problems and approaches that have influenced the course of Western philosophy from Kant in the eighteenth century up through the twenty-first century. This book examines many aspects of Leibniz's work and life. This expanded edition adds new chapters that explore Leibniz's revolutionary deciphering machine; his theoretical interest in cryptography and its ties to algebra; his thoughts on eternal recurrence theory; his rebuttal of the thesis of improvability in the world and cosmos; and an overview of American scholarship on Leibniz